Tafsir Maqāshidī: Telaah Terhadap Kitab Tafsir al-Ahkam karya Abdul Halim Hasan - Mumin Roup; Muhammad Muammar Alwi; Akmal Rizki Gunawan Hsb (AL QUDS : Jurnal Studi Alquran dan Hadis, 2022)
Tafsir Maqāshidī: A Study of the Book of Tafsir al-Ahkam by Abdul Halim HasanThis study aims to analyze the interpretation in the Book of Tafsir al-Ahkam Abdul Halim Hasan related to the relationship between Muslims and non-Muslims based on maqāshidī interpretation. To examine Abdul Halim's interpretation, in this case the researcher uses the casuistic method, namely choosing the interpretation results as a sample that represents the methodological conclusions. The overall data in this study is written library research or library research, either in the form of books, research reports or journals related to research. The findings of this study indicate the application of maqāsid al-shari'ah elements in the Book of Tafsir al-Ahkam Abdul Halim Hasan, this can be seen from his interpretation of verses relating to Muslim and non-Muslim relations, such as; interfaith marriages, make infidels as guardians and insult the God of other religions. In Abdul Halim's interpretation it is explained that the prohibition of interfaith marriages is seen in maqāsid al-shari'ah, there is prudence in maintaining or maintaining religion and the prohibition of making non-believers as guardians for fear of betrayal, while the prohibition of insulting God of other religions aims to prevent damage between adherents of religions